THE APPLICATION OF MIND MAPPING TECHNIQUE TO INCREASE STUDENTS’ READING COMPREHENSION AT THE SEVENTH GRADE OF SMP - Devilito Tatipang; Elizabeth Z. Oroh; Nihta V. F. Liando (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of the study was to find out whether the application of Mind Mapping Technique can increase Students’ Reading Comprehension or not. This study was conducted at SMP N 3 Sangtombolang. The design of this study was pre-experimental with one group pre-test and post-test design. The subject in this study was class VII in academic year 2020/2021, which consisted of 15 students. The data of this study were collected through cloze test. The data were analysed by comparing the mean score of the tests. The mean score of the post-test (T2) is higher 83.7 than those of the pre-test (T1) 26.6. This heads to the conclusion that the application of mind mapping technique could increase students’ reading comprehensio